2018
DOI: 10.1089/ars.2016.6968
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide As a Potential Target in Preventing Spermatogenic Failure and Testicular Dysfunction

Abstract: HS plays an important role in spermatogenic failure and testicular dysfunction mainly by its anti-inflammatory and antioxidative effects. Antioxid. Redox Signal. 28, 1447-1462.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(77 citation statements)
references
References 45 publications
1
75
1
Order By: Relevance
“…Nowadays, H 2 S has been generally recognized as a novel “gasotransmitter” with similar properties of nitric oxide and carbon monoxide. Moreover, previous study has verified the powerful ability of antioxidation by H 2 S in several systems …”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Nowadays, H 2 S has been generally recognized as a novel “gasotransmitter” with similar properties of nitric oxide and carbon monoxide. Moreover, previous study has verified the powerful ability of antioxidation by H 2 S in several systems …”
Section: Introductionmentioning
confidence: 79%
“…H 2 S has potential ability of antioxidative stress in different tissues. The latest study found that H 2 S suppressed oxidative stress to inhibit NLR family pyrin domain containing 3 (NLRP3) inflammasome activation in macrophages, to attenuate myocardial hypertrophy and fibrosis, to alleviate spermatogenic failure and testicular dysfunction and to suppress aortic atherosclerotic plaque formation . Importantly, H 2 S also exhibited antioxidative effect on skin.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that CSE is expressed in sertoli cells, spermatogonia and epididymis of rats. For instance, the therapeutic effects of H 2 S are reported in erectile dysfunction, heat-induced injury in testicular germ cells and diabetes-induced testicular dysfunction (Li, Xie, Chua, Wong, & Bian, 2015;Wang et al, 2018;Zhu et al, 2011). D,L-propargylglycine (PAG) is a well-known CSE enzyme inhibitor, which is used in this study to explore the exact role of CSE in this model of rat varicocele.…”
mentioning
confidence: 99%
“…Importance of H 2 S on normal testes function, for example spermatogenesis, has been shown by the very recent data of Wang and co‐workers who reported that stress induced reductions of endogenous H 2 S production and CBS expression in testes, is followed by impaired spermatogenesis and a defective blood testicular barrier. They further showed that the exogenous administration of H 2 S can exert protective effects in lipopolysaharide induced testicular pathologies, and could relieve the spermatogenic failure.…”
Section: Physiological Signaling Of Rss In Male Reproductive Eventsmentioning
confidence: 95%
“…Namely, reactive oxygen and nitrogen species (ROS and RNS, respectively) have appeared as key players in crucial sperm reproductive functions. In addition, during the last decade, reactive sulfur species (RSS), firstly hydrogen sulfide (H 2 S) was identified and characterized as novel important redox signaling molecule in male reproductive system …”
Section: Introductionmentioning
confidence: 99%